Early Sitting, Standing, and Walking in Conjunction With Contemporary Bobath Approach for Stroke Patients With Severe Motor Deficit. Issue 2 (March 2014) - Tang, Qingping; Tan, Lihong; Li, Baojun; Huang, Xiaosong; Ouyang, Chunhong; Zhan, Hailan; Pu, Qinqin; Wu, Lixiang
Abstract : Background: The commonly used therapeutic approach, the contemporary Bobath approach (CBA), is not sufficient to restore independent locomotion for individuals with severe motor deficit (SMD) after stroke. Therefore, we propose that the early sitting, standing, and walking in conjunction with the CBA (ECBA) be used to treat individuals with SMD after stroke.Objective: To investigate whether ECBA may enhance mobility and balance in subjects with SMD after stroke.Methods: Thirty-three men and 15 women, aged 60 to 74 years, with SMD after stroke were recruited for the study. CBA or ECBA was performed with the subjects 5 times per week in 50-minute sessions for 8 weeks. The Stroke Rehabilitation Assessment of Movement (STREAM) and the Berg Balance Scale were implemented before treatment and at 4 and 8 weeks after treatment, respectively.Results: The STREAM scores indicated that ECBA was more efficient than the CBA intervention for lower extremity mobility, F (1, 46) = 24.0, P < .001, and basic mobility, F (1, 46) = 102.6, P < .001. Overall STREAM scores were higher in the ECBA group, F (1, 46) =24.1, P < .001, after 8 weeks of therapy. Balance scores of the ECBA subjects were higher than those of the CBA subjects after 8 weeks of therapy, F (1, 46) = 73.1, P < .001. However, there was no difference in upper extremity mobility between the 2 groups.Conclusion: ECBA is a valuable intervention to improve lower extremity mobility, basic mobility, and balance ability for individuals with SMD after stroke.